2023
DOI: 10.3390/molecules28073221
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Bioactive Phenolic Molecules and Antioxidant Properties of Beer: Emerging Trends

Abstract: Beer is one of the oldest and most common beverages worldwide. The phenolic contents and antioxidant properties of beer are crucial factors in evaluating its nutritional quality. Special beers brewed with the addition of adjuncts are gaining in consumer preference, in response to demands for healthy food and new gustatory and olfactory stimuli. Many studies recently dealt with functional beers brewed with the addition of adjuncts. This review focuses on bioactive molecules, particularly the composition of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 182 publications
0
3
0
Order By: Relevance
“…Several types of beer, both conventional and with the addition of fruits, spices, or natural food during the fermentation process (namely special beer), have been studied for their antioxidant power [ 27 ]. These bioactivities may arise from the phytochemicals provided by hops (e.g., bitter acids and polyphenols) during the beer fermentation [ 28 ], along with the addition of flavouring and preservative agents to beer for improving its gustatory, olfactory, and visual features [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several types of beer, both conventional and with the addition of fruits, spices, or natural food during the fermentation process (namely special beer), have been studied for their antioxidant power [ 27 ]. These bioactivities may arise from the phytochemicals provided by hops (e.g., bitter acids and polyphenols) during the beer fermentation [ 28 ], along with the addition of flavouring and preservative agents to beer for improving its gustatory, olfactory, and visual features [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous natural bioactive molecules, such as polyphenols, flavonoids, alkaloids, and terpenes, have been discovered and studied as potential therapeutic candidates to act against neurodegenerative diseases [ 1 ]. One such compound belonging to the group of flavonoids is xanthohumol (Xn, 2′,4′,4-trihydroxy-6′-methoxy-3′-prenylchalcone), found in the hop flower ( Humulus lupulus ), one of the main ingredients of beer, which contributes at least 30% of its polyphenol content [ 2 ]. This prenylated chalcone has been reported to have anti-inflammatory [ 3 , 4 ], antioxidant [ 5 , 6 , 7 ], and antiproliferative properties [ 8 ] on various cell lines and animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Archeological research has found evidence of beer consumption in China dating back as far as 9,000 years ( 1 ). In response to consumer demand for new taste, smell, and visual stimuli, and for a variety of beer types, including non-alcoholic beers, beers produced by producers who add fruits, spices, vegetables, and natural foods to the fermentation process are becoming very popular around the world ( 2 ). At the same time, the health properties of beer that cannot be ignored are also gaining attention.…”
Section: Introductionmentioning
confidence: 99%